Procoagulant activity induced by transcatheter closure of atrial septal defects is associated with exposure of phosphatidylserine on microparticles, platelets and red blood cells. Issue 2 (August 2015) - Ding, Wenbo; Kou, Junjie; Meng, Huan; Kou, Yan; He, Zhangxiu; Cao, Muhua; Wang, Lixiu; Bi, Yayan; Thatte, Hemant S.; Shi, Jialan
Abstract The mechanism of hypercoagulable state following transcatheter closure of atrial septal defects (ASDs) remains unclear. We evaluated the exposure of phosphatidylserine (PS) on released microparticles (MPs) and also the cells of their origin from peripheral blood, and the associated increase in procoagulant activity (PCA) following transcatheter ASD closure. We demonstrate that PS+ MP levels were elevated immediately after device implantation (P < 0.002), peaked at 24 hour (P < 0.002), and persisted at high levels for 1-week post procedure (P < 0.002). Flow cytometry analysis indicated that PS+ MPs were mainly derived from platelets, endothelial cells, and the red blood cells (RBCs). Concomittantly, PS+ platelet and RBC count also increased after transcatheter closure of ASDs, while PS+ leukocytes levels remained the same. Compared to the baseline, coagulation time of PS+ MPs, platelets, and RBCs at 24 hours post procedure decreased by about 18.7% (P < 0.004), 21.5% (P < 0.001), and 26.8% (P < 0.001), respectively. Intrinsic factor Xa and prothrombinase were produced abundantly by platelets, RBCs, and MPs leading to materialization of fibrin by 24 hours. Additionally, Xase complex formation and thrombin generation was inhibited by about 74% by the addition of lactadherin to the assays. Our results thus demonstrate that PS exposure on MPs, platelets, and RBCs play an important role in hypercoagulability following transcatheter ASD closure.